Radiological Properties of Some Chemotherapy Drugs for Electron, Proton and Carbon Ion Interactions in the Energy Region 10 keV – 400 MeV - Büyükyıldız, Mehmet; Türemiş, Murat (My University, 2023)
Radiological properties of some chemotherapy drugs such as Doxorubicin, Vincristine, Teniposide, Azathioprine, Etoposide, Cyclophosphamide, Vinblastine, Bleomycin were investigated according to total electron interaction and some heavy charged particle interactions on behalf of effective atomic numbers (Zeff) and electron densities (Neff) for the ?rst time. Calculations were performed for total electron, proton and C ion interactions, commonly used in therapy, in the energy region 10 keV- 400 MeV. Variation of Zeffs and Neffs of given drugs was studied according to energy of electron or heavy charged particles and significant variations were observed for all types of interaction in the given energy region. The highest values of Zeff were found in the different regions of energy for different particle interactions remarkably and variation in Neff seems approximately to be same with alteration in Zeff for the investigated drugs. Also, Zeff values of all drugs were plotted together and compared with each other for electron, proton and C ion interactions in the continuous energy region. Maximum and minimum values of Zeff were observed in Azathioprine (6.14) and Vinblastine (2.25) for electron interaction and proton interaction in the continuous energy region, respectively. The obtained results were compared with the Phy-X/ZeXTRa program between 10 keV-15 MeV energy region.
Keywords: Effective atomic number; Charged particles; chemotherapy drugs; electron density